Wine tourism of Tokaj- hegyalja - Törökné Kiss, Klára (Acta Agraria Debreceniensis, 2014)
The wine is still in Hungary in Hungarian history, culture, and one of the key elements of the economy are considered . Last, but not to the point of producing and selling the wine regions of livelihoods. Thousands of years in wine-producing traditions preserved in the modern winemakers, wine competitions demonstrate their skills. The Tokaj wine region of the World’s major and significant wine regions in Hungary.